Investigating the influence of aquifer heterogeneity on the potential for thermal free convection in the Yarragadee Aquifer, Western Australia - Irvine, D.; Sheldon, H.; Simmons, C.; Werner, A.; Griffiths, Cedric (2014)
The potential for thermal convection in aquifers is strongly influenced by permeability. Permeability is highly heterogeneous within aquifers, and spatial distributions of permeability are rarely well constrained by measurements, making it difficult to determine the potential for thermal convection in a given aquifer. In this study, this difficulty is overcome through the use of a stratigraphic forward model (SFM). The SFM simulates the processes of deposition, burial and compaction of the aquifer, yielding a geologically plausible permeability field that is conditioned through measured permeability-porosity relationships. The aim of this study is to determine the influence of aquifer heterogeneity on the potential for thermal convection in the Yarragadee Aquifer, Western Australia. Permeability distributions from the SFM of the Yarragadee Aquifer are analysed through calculation of the thermal Rayleigh number (a stability criterion) from vertically averaged permeability, and numerical hydrothermal simulations with permeability distributions taken from the SFM. Results from the numerical simulations demonstrate that thermal convection can occur with the inclusion of geologically informed heterogeneity. These findings are supported by Rayleigh number calculations that indicate that convection is most likely to occur on the eastern side of the aquifer where it is thick and has high average permeability.